Relationships within the Araceae: comparison of morphological patterns with molecular phylogenies. - Natalie, Cusimano; Josef, Bogner; Simon J., Mayo; Boyce, P.C; Wong, Sin Yeng; Michael, Hesse; Wilbert L. A., Hetterscheid; Richard C., Keating; Jim C., French (American Journal of Botany, Inc., 2011)
Premise of the study: The first family-wide molecular phylogeny of the Araceae, a family of about 3800 published species in 120 genera, became available in 1995, followed by a cladistic analysis of morpho-anatomical data in 1997. The most recent and comprehensive family-wide molecular phylogeny was published in 2008 and included species from 102 genera. We reanalyzed the molecular data with a more complete genus sampling and compared the resulting phylogeny with morphological and anatomical data, with a view to contributing to a new formal classification of the Araceae.